CROP-LIVESTOCK INTEGRATION SYSTEM IN THE CERRADO (REMUNOM, 2024)
Crop-livestock integration (CLI) in the Cerrado represents an innovative agricultural practice that combines grain cultivation and livestock farming in the same area, promoting the sustainability and efficiency of agricultural production. This approach aims to optimize the use of natural resources, improve soil quality, reduce the incidence of pests and diseases, and increase the profitability of rural producers. The study analyzed several CLI systems, including Barreirão, Santa Fé, Pontal, São Francisco and Agrosilvopastoral, each adapted to the specific conditions of the Cerrado. It was found that CLI offers significant economic, environmental and social benefits, standing out as an effective strategy for the conservation of natural resources, the sustainable intensification of production and the promotion of rural development. Research and rural extension are essential for the dissemination of knowledge and the training of producers, ensuring the successful implementation and consolidation of CLI as a sustainable practice.